Formative research and achievement in students of a public university - Lima - Paucca Gonzales, Nelson (2021)
The article responds to the general objective: to determine the relationship between formative research and the accomplishment of competencies for the students of the faculties of Technology, Primary Education, Social Sciences and Humanities of the National University of Education. In order to obtain the results, a basic quantitative non-experimental focus was taken into account, as well as a correlational design, and in addition the use of an analytical and hypothetical deductive methodology. The population was made up of 3, 275 with a sample of 344 male and female students. The information was obtained by way of surveys and a questionnaire with the Likert scale. The statistics were treated using Microsoft Excel and SPSS-25 software, with the results being analyzed in two different moments, by way of the descriptive statistics and the proof of the hypothesis using inferential Spearman Rho statistics which demonstrated a relationship of moderate magnitude (r=.724) and a significant statistical value (P = .000 less than 0.05). Therefore, a direct and significant relationship exists between the variables of formative research and the accomplishment of competencies for the students of the faculties of Technology, Primary Education, Social Sciences and Humanities of the National University of Education during the 2020 Academic Cycle.